A novel Schiff base-containing branched polysiloxane as a self-crosslinking flame retardant for PA6 with low heat release and excellent anti-dripping performance. (15th February 2020) - Fan, Shuo; Peng, Bo; Yuan, Ruchao; Wu, Dequn; Wang, Xueli; Yu, Jianyong; Li, Faxue
Abstract: Preparing flame-retardant polyamide 6 (PA6) composites with low addition of flame retardant remained one of the biggest concerns nowadays. In this work, a novel aromatic Schiff base-containing branched polysiloxane (PCNSi) with high thermal stability and great capacity of charring was first synthesized as a self-crosslinking flame retardant, and then PA6/PCNSi composites were prepared through melt blending with different contents of PCNSi. Inspiringly, a sharp reduction of about 48.9% in peak heat release rate (PHRR) was found for PA6 composite with only 6 wt% of PCNSi in contrast with PA6, and serious melt-dipping behavior of PA6 was suppressed totally as 4 wt% of PCNSi was added into PA6. The formation of a self-extinguished layer was considered as the essential factor for reinforcing the flame retardancy of PA6. This layer was generated under the synergistic effects of the cross-linking reaction of Schiff base structure and thermo-oxidative degradation of polysiloxane units in PCNSi. These composites also presented similar mechanical properties to PA6 due to the low addition of PCNSi and good interfacial interactions between PCNSi and PA6. Graphical abstract: Image 1 Highlights: An aromatic Schiff base-containing branched polysiloxane (PCNSi) was prepared as a self-crosslinking flame retardant. A sharp reduction of 48.9% in peak heat release rate (PHRR) was achieved for PA6 when 6 wt% of PCNSi was added. The serious melt-dipping behavior of PA6 was suppressed totally only with 4 wt% of PCNSi. PA6/PCNSi composites still retained the close mechanical properties to PA6.